2002
DOI: 10.1089/104303402320139005
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Targeted Salmonella Expressing Cytosine Deaminase as an Anticancer Agent

Abstract: The study was designed to evaluate whether TAPET-CD, an attenuated strain of Salmonella typhimurium ex pressing Escherichia coli cytosine deaminase (CD), was capable of converting nontoxic 5-fluorocytosine (5-FC) to the active antitumor agent 5-fluorouracil (5-FU). The antitumor effect of TAPET-CD plus 5-FC against subcutaneously implanted colon tumors was also evaluated. TAPET-CD was given to tumor-bearing mice by a single bolus intravenous administration followed with 5-FC by intraperitoneal administration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 15 publications
2
83
0
Order By: Relevance
“…This 19 F MRS analysis revealed the absence of 5-FU and only small amounts of catabolites in the liver, at least up to 2 h after the in vivo measurements. Our results agree with the observations made by King et al, (2002) using high-performance liquid chromatography. The difference between the small catabolite levels in our study and the large levels usually found with conventional 5-FU chemotherapy, is obvious for two reasons: (1) it is expected that the 'leakage' of 5-FU from the tumour microenvironment into the systemic circulation is poor (eg, indirectly shown by Wallace et al, 1994), and (2) this type of conversion occurs mainly in the liver and little FBAL enters the systemic circulation (discussed by eg, Prior et al, 1990).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This 19 F MRS analysis revealed the absence of 5-FU and only small amounts of catabolites in the liver, at least up to 2 h after the in vivo measurements. Our results agree with the observations made by King et al, (2002) using high-performance liquid chromatography. The difference between the small catabolite levels in our study and the large levels usually found with conventional 5-FU chemotherapy, is obvious for two reasons: (1) it is expected that the 'leakage' of 5-FU from the tumour microenvironment into the systemic circulation is poor (eg, indirectly shown by Wallace et al, 1994), and (2) this type of conversion occurs mainly in the liver and little FBAL enters the systemic circulation (discussed by eg, Prior et al, 1990).…”
Section: Discussionsupporting
confidence: 93%
“…Using in vitro analysis of bacterial lysates, we also clearly demonstrated the positive correlation between the number of TAPET-CD and the amount of 5-FC that is converted to 5-FU for a given incubation period. Second, the TAPET-CD persist in the tumours without the need for a repeat injection, similar to the findings of King et al, (2002) and Mei et al, (2002). Indeed, in the present study, the production of 5-FU after the i.p.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…19,20,24 CD is an enzyme found in both bacteria and fungi, but not in mammalian cells. It converts 5-fluorocytosine (5-FC), an antifungal agent with limited systemic toxicity, to 5-fluorouracil (5-FU).…”
mentioning
confidence: 99%